1998
DOI: 10.1524/ract.1998.80.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Patterns of Pionic X Rays Emitted from Some Organic Compounds

Abstract: Pionic atom / Pionic X rays / Negative pion transfer process / Cascade calculation / Pionic hydrogen atom SummaryPionic X-ray intensity pattems of the Balmer series have been studied in the carbons and oxygens of alcohols, carboxylic acids, alkanes, etc. The X-ray intensity ratios (4-2)/(3-2) in the carbons of both alcohols and carboxylic acids decrease with the number of carbon atoms and approach that of Polyethylene. On the other hand, the ratios in oxygen remain constant. The variations in the intensity rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Shinohara et al [29] reported that the pion capture probability of hydrogen atoms of hydrocarbon molecules varied with the molecular structure. Furthermore, they reported that the pionic X-ray intensity pattern of the Balmer series varied with the molecular structure of hydrocarbon molecules [30]. For condensed systems, they reported the chemical effect on the pion transfer reaction in mixtures of carbon tetrachloride and benzene or cyclohexane [31].…”
Section: Introductionmentioning
confidence: 99%
“…Shinohara et al [29] reported that the pion capture probability of hydrogen atoms of hydrocarbon molecules varied with the molecular structure. Furthermore, they reported that the pionic X-ray intensity pattern of the Balmer series varied with the molecular structure of hydrocarbon molecules [30]. For condensed systems, they reported the chemical effect on the pion transfer reaction in mixtures of carbon tetrachloride and benzene or cyclohexane [31].…”
Section: Introductionmentioning
confidence: 99%